The Effects of Smartphones on Child Health - Tanveer, Fahad (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Over the last ten years, technology has advanced significantly, and more people throughout the world have access to smartphones. Because of the increased use of technology, including cellphones, children are leading more sedentary lifestyles. Long-term smartphone usage has sparked further questions about possible changes in spinal posture, continual neck flexion, restrictions on neck motions, and declines in pulmonary function. According to data from the Pew Research Center, the proportion of smartphone users in emerging and developing nations increased quickly from 21% in 2013 to 37% in 2015. By 2020, the numbers are projected to be 6.4 billion smartphone subscribers, or around 70% of the world’s population. In the US, 84% of teenagers aged 13 to 19 and 79% of children aged 9 to 12 possess cellphones, and by the time they are 12 years old, they use their smartphones on average for five hours each day [1]. Mobile phones have reportedly become a need for young people and children, according to Pakistani research on cell phone habits among teens in southern Punjab [2]. Due to the rise in smartphone use among kids and teenagers, their musculoskeletal systems are significantly impacted. Obesity, poor posture, and thoracic limitation brought on by muscular imbalances are linked to the decline in fundamental physical fitness. The aforementioned issues often lead to a decline in pulmonary function. Musculoskeletal problems are likely to worsen with time, particularly if users see their cellphones with their heads flexed. Excessive smartphone usage may also affect the cervical angle scan, especially if users don’t keep their posture neutral, which might put more strain on the cervical spine. Constant forward neck flexion when using a smartphone causes the lower cervical spine to bend excessively, which is linked to decreased lung function and respiratory muscle power. In terms of psychology, excessive smartphone usage weakens social bonds and increases loneliness, sadness, and social anxiety, leading to mental immaturity, emotional instability, inattentiveness, and lack of self-control in kids. Increased sleep issues are also linked to increased mobile phone use. Despite certain benefits, the increased use of cell phones has raised a lot of concerns over their negative impacts on academic performance, health, and character development. Several health issues are also related to increased smartphone usage in children. To maintain posture, cranio-cervical and improved respiratory function, instruction on optimal smartphone using posture as well as information on the implications of prolonged smartphone usage are required.